(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores innovative pedagogical approaches for teaching organic chemistry at the university level. Traditional teaching methods in organic chemistry often focus on rote memorization, which can lead to student disengagement and difficulties in applying concepts to new situations. This paper examines several modern teaching technologies and methodologies that promote deeper understanding, including problem-based learning, flipped classroom approaches, digital simulation tools, collaborative learning strategies, and visualization techniques. Implementation challenges and benefits are discussed, along with recommendations for integrating these approaches into existing curricula. Evidence from recent educational research suggests that these innovative pedagogical approaches can significantly enhance student comprehension, retention, and enthusiasm for organic chemistry.